Cancer and body image: loss of female identity - Carolina Linard de Oliveira; Francisca Poliana Alves de Sousa; Cíntia de Lima Garcia; Marta Regina Kerntopf Mendonça; Irwin Rose Alencar de Menezes; Francisco Elizaudo de Brito Junior (Rev Rene)
The aim of this study was to learn about the feelings and possible difficulties faced by women in anti-neoplastic chemoterapy concerning body image changes. 14 women in treatment in an oncology reference hospital in Cariri-CE, Brazil participated in the study. The data collection took place between May and July 2009 through a semi-structured interview. Later, data were classified according to the speech of the subjects. There was prevalence of women aged between 38 and 48 years, in a stable marital relationship and with children. Most of them demonstrated optimism concerning the disease, occasionally with feelings of fear and anxiety. As for the body it was verified implicit dissatisfaction in the speeches. It was reported that, after the diagnosis, changes happened in their lives, including body care that made them gain new values. It is pointed out the need of considering the psycho-social aspects in the approach of patients with cancer, seeking a more integral and human assistance to such patients.